An innovative solution to raise public awareness using a mobile colorectal clinic - The 'bowel bus'. (March 2017) - Naguib, N.; Lewis, M.; Iredale, R.; Pugh, R.; Haray, P.N.
Abstract: Introduction: Colorectal cancer is the fourth most common cancer in the United Kingdom; however, figures show that the uptake for bowel cancer screening lags behind other cancer screening programmes. Methods: This is a report of a multi-staged development of an outreach colorectal clinical community service provided through a Mobile Unit (a Bowel Bus). The unit delivers a one-stop colorectal clinic that provides a rapid access pathway to members of the public who have concerns about, or symptoms of, bowel cancer. The aims of the project were to increase public awareness about colorectal cancer and to provide an outreach clinic as a supplement to the hospital based colorectal clinic. This service is a result of collaborative efforts between Tenovus Cancer Care (TCC) and the colorectal surgery department of the local NHS Hospital. Results: During one year, the Bowel Bus has provided services to 772 members of the local community. 244 patients were examined by the colorectal nurse specialist including 66 drop-in patients and 135 patients referred by the GPs. The service led to decrease in the waiting list for routine referrals to be seen in the colorectal clinic at the hospital from a mean of 10.5 weeks–5.9 weeks. A feedback questionnaire from 180 patients, used to audit the quality of the service, has confirmed an overwhelming satisfaction with the service. Conclusion: The Mobile Unit is a novel solution to addressing the ever increasing demand for specialist outpatient services without compromising the quality of care whilst enhancing the patient experience.